Characterization of capsular polysaccharides and their glycoconjugates by hydrodynamic methods - Harding, Stephen E.; Abdelhameed, Ali Saber; Gillis, Richard B.; Morris, Gordon A.; Adams, Gary G. (Springer, 2015)
Hydrodynamic methods are relevant for the characterization of carbohydrates such as capsular bacterial polysaccharides or glycoconjugates in solution. This chapter focuses on the following hydrodynamic methods: sedimentation velocity analytical ultracentrifugation (SV AUC), dynamic light scattering (DLS), sedimentation equilibrium analytical ultracentrifugation (SE AUC), size exclusion chromatography coupled to multi-angle light scattering (SEC-MALS), and capillary viscometry—intrinsic viscosity measurement. The chapter highlights the general principle of these five methods, describes experimental details, and specifies advances in the last years.